A Tribute to Dr. Ronald Hardy for his Contribution to Aquaculture Nutrition. - Cruz Suárez, Lucía Elizabeth; Ricque Marie, Denis (Universidad Autónoma de Nuevo León, 2011)
Ronald William Hardy was born in 1947 in Vancouver, Canada. He comes from a very academically able Canadian/Scottish family. His grandparents came from Scotland and moved to Vancouver in 1909. In his father´s family there were doctors, nurses and also missionaries in Canada near Alaska. Ron´s father worked in agriculture communities around Seattle (an expert in poultry science), and used to take his 6 years old son salmon fishing, that was Ron´s first connection with salmon and trout. His mother came from a family of Scottish farmers, and then scientists; she was a Microbiologist and worked on tuberculosis. Ron took pre-medicine curriculum for 4 years, receiving his BS in Zoology in 1969 at the University of Washington. He took many jobs, including on farms and railroads, to pay for his college education. In 1970 he married Elizabeth the future mother of his daughters (Anna and Clare). Then in 1973, he obtained a M.S. in Animal Sciences/Nutrition at Washington State University; his thesis subject was “Studies on factors in rye which cause growth depression in chicks”. One day at the University Library he found the book of Dr. Halver on fish nutrition and, discovering the important gap in this area with respect to poultry, porcine and bovine nutrition, realized the huge potential of this new activity. Halver´s book was his second inspiration… It was at this time that he commenced his life‟s work on the nutrition of fish, graduating with a PhD in Fisheries at the University of Washington, Seattle (1978). Hardy‟s PhD dissertation subject was “Effects of dietary protein and pyridoxine levels on growth and disease resistance of chinook salmon”, having as mentors Dr. Halver (biochemistry and nutrition) and Dr. Brannon (salmon biology).